Evaluating the impact of the use of the Model of excellence reference model by Brazilian electricity distributors - Carrasco, A.; Andrade, M. A. P.; Rosa, A.; M. Filomena Teodoro (ICRA9: 9th International Conference on Risk Analysis, 2022)
The article evaluates the impact of the use of the excellence management model (EMM) in Brasil by electricity distribution companies and their impact on customer satisfaction, that is, on the index of consumer satisfaction evaluation (ICSE). A total of 10 year were evaluated for the use of the model in groups of companies with different levels of model implantation (users, indifferent, engaged and winning) using statistical methods. As result, it was verified the existence of differences between the groups revealed the correct decision by the use of the model seen by this view. The results can be used by similar organizations or other industries